2014
DOI: 10.1128/aac.01167-13
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Host Defense Peptide Prodrugs as Neutrophil Elastase-Dependent Anti-Infective Agents for Cystic Fibrosis

Abstract: Host defense peptides (HDPs) are short antimicrobial peptides of the innate immune system. Deficiencies in HDPs contribute to enhanced susceptibility to infections, e.g., in cystic fibrosis (CF). Exogenous HDPs can compensate for these deficiencies, but their development as antimicrobials is limited by cytotoxicity. Three HDP prodrugs were designed so their net positive charge is masked by a promoiety containing a substrate for the enzyme neutrophil elastase (NE). This approach can confine activation to sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 51 publications
(85 reference statements)
6
41
0
Order By: Relevance
“…Whereas the main focus of our in vitro experiments was the maintenance of surfactant and antimicrobial activities of potential AMP-based surfactant preparations, it should be noted that it has also been reported that AMP can have cytotoxic effects toward mammalian cells (10,26,33). Such effects could potentially limit the therapeutic applicability of this approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the main focus of our in vitro experiments was the maintenance of surfactant and antimicrobial activities of potential AMP-based surfactant preparations, it should be noted that it has also been reported that AMP can have cytotoxic effects toward mammalian cells (10,26,33). Such effects could potentially limit the therapeutic applicability of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…To accomplish this goal, surfactant adsorbs and spreads rapidly to form a surface film consisting of lipid-condensed and lipid-expanded regions at the air-liquid interface, which upon lateral compression forms a stable multilayer structure capable of reducing surface tension values to near 0 mN/m (10). Through its ability to spread throughout the lung and open up collapsed lung areas, exogenous surfactant therapy has been shown to reduce mortality of premature infants afflicted with neonatal respiratory distress syndrome (10,11).…”
mentioning
confidence: 99%
“…Both protocols for collection were approved by the Beaumont Hospital Research (Ethics) Committee. The NE content was determined by measuring the cleavage of N-methoxysuccinyl-Ala-Ala-Pro-Val-p-nitroanilide as described previously (16).…”
Section: Methodsmentioning
confidence: 99%
“…The colocalization of P. aeruginosa and NE allows the potential cytotoxic effects of the AMPs (pro-HB43 and pro-P18) to be confined to the site of infection (16). However, a significant scope to improve the selectivity of pro-AMPs remained.…”
mentioning
confidence: 99%
See 1 more Smart Citation